Inhibitors of leishmania mexicana phosphoglycerate mutase identified by virtual screening and verified by inhibition studies - Ahmad Fuad, Fazia Adyani; Houston, Douglas Robert; Michels, Paul A M; Fothergill- Gilmore, Linda A.; Walkinshaw, Malcolm Douglas (Penerbit Universiti Kebangsaan Malaysia, 2016)
Cofactor-independent phosphoglycerate mutase has been proposed as a therapeutic target for the treatment of trypanosomatid diseases. In this paper, we report the identification of compounds that could potentially be developed as selective inhibitors of cofactor-independent phosphoglycerate mutase from Leishmania mexicana (LmiPGAM). Virtual screening was used in this search, as well as compounds identified by high-throughput screening. A ligand-based virtual screen programme, ultra fast shape recognition with atom types (UFSRAT), was used to screen for compounds resembling the substrate/product, before a structure-based approach was applied using AutoDock 4 and AutoDock Vina in a consensus docking scheme. In this way eight selected compounds were identified. In addition, three compounds from the Library of Pharmacologically Active Compounds (LOPAC) were selected from the published results of high-throughput screening of this library. The inhibitory effects of these compounds were tested at a fixed concentration of 1 mM. The results showed that seven compounds inhibited LmiPGAM activity and of these, two compounds (one each from high-throughput and virtual screening) showed substantial inhibition (i.e. 14% and 49% remaining activity, respectively). Taken together, the findings from this study indicate that these compounds have potential as novel inhibitors that specifically target LmiPGAM.